1999
DOI: 10.1074/jbc.274.49.35089
|View full text |Cite
|
Sign up to set email alerts
|

Yeast SMF1 Mediates H+-coupled Iron Uptake with Concomitant Uncoupled Cation Currents

Abstract: Metal ions are important for all living cells. In man, metal ion deficiency leads to anemia (1), whereas metal ion overload is toxic and leads to hemochromatosis (3), Menkes' disease (2), Wilson's disease (4), and neurodegenerative diseases (5-7). Metal ions such as iron, manganese, zinc, and cobalt are involved in many catalytic reactions, gene regulation, and signal transduction pathways (8 -10). An adequate supply of metal ions to cells is important and is provided by specialized transporters.The recently c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
126
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 37 publications
7
126
0
Order By: Relevance
“…Expression of Smf1p in Xenopus oocytes demonstrated that this protein mediates H ϩ -dependent divalent metal ion transport (14). In addition, a large Na ϩ leak through Smf1p was observed, and sodium competed with the activity of metal ion uptake.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Expression of Smf1p in Xenopus oocytes demonstrated that this protein mediates H ϩ -dependent divalent metal ion transport (14). In addition, a large Na ϩ leak through Smf1p was observed, and sodium competed with the activity of metal ion uptake.…”
mentioning
confidence: 89%
“…Previously we reported that Na ϩ inhibits metal ion transport by Smf1p and prevents growth of the wild type or ⌬SMF2 strains in the present of EGTA (14). Addition of sodium to the manganese uptake system as described in Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…These constructs were expressed in the yeast smf1 mutant, deficient in a broad range metal transporter nramp homolog (40,41). To test for functional complementation, smf1 mutants transformed with pYES2 containing either Lenramp1, Lenramp3, or empty control vector and, as positive control, wild type yeast were spotted in different dilutions on minimal medium in the presence of 5, 10, 20, and 50 mM divalent metal chelator EGTA.…”
Section: Identification Of Nramp Metal Transportermentioning
confidence: 99%
“…Notably, DMT1, identified as an intestinal iron transporter, as well as DMT1 family members in other species (eg, SMF1 in yeast), can transport iron, manganese, zinc, cobalt, and copper. 39,40 The Fet4 transporter in yeast, 41 IRT1 in plants, 42 as well as ZIP14 in mammals 43 transports other transition metals in addition to iron.A recent study has shown that Fpn can transport manganese, suggesting that Fpn may accept other metals as substrates. 44 Our data show that Fpn has modest zinc transport activity.…”
mentioning
confidence: 99%